Polanyi defanged - Turner, Stephen (Social Studies of Science (Sage Publications, Ltd.), 2012)
A literary criticism of the book "Michael Polanyi and His Generation: Origins of the Social Construction of Science," by Mary Jo Nye is presented. The author discusses the significance of Michael Polanyi in the history of science studies and provides insight on his life and his relationship with his brother Karl. He analyzes how the book presents the origins of science studies, Polanyi’s activities as an economist, and his fight against Communism.
Sociology
Keywords: Dahomey and the Slave Trade; James Bryant Conant; Karl Polanyi; Michael Polanyi & His Generation: Origins of the Social Construction of Science (Book); NYE; Mary Jo; POLANYI; Michael; 1891-1976; communism & science; economists; planning of science; science - study & teaching